Mediações comunicativas do trabalho “criativo”: novos caminhos, mapas antigos - Costa, Nathália Drey (2022)
The thesis entitled Communicative mediations of “creative” work: new paths, old maps starts from the knowledge that work goes by an important cultural and communicational changes in our time and the guide-question considered the communicational dimension of work by the Martín-Barbero's mediations. The objective of this thesis was to investigate the communicative mediations of work in the Brazilian creative industry and build a communicational map about creative work, based on an appropriation and interpretation of the third map prepared by Martín-Barbero (2009) and systematized by Maria Immacolata Vassallo de Lopes (2009; 2014). Based on this appropriation, a reading of the map was proposed with an analysis of creative work through communicative mediations. In this research, it's important to point that the term “creative” associated with "work" isnt in a neutral way, but understood as a neoliberal perspective that associates creativity with a capitalist production. The methodology used was a combination of techniques in different periods (2018, 2019 and 2020) consisting of an interview, an online questionnaire with 40 respondents and 11 online work diaries. The adaptation of the methods to the online format supported the period of the Covid-19 pandemic (2020). Finally, we have the mobilities of the creative worker (the neoliberal subjectivity of a multifaceted working class) mediated by an adjectival identity (focused on autonomy and the idea of flexibility) and by a cognitivity that negotiates creative references (through innovation and repetition ) and creative subjectivities (motivation, purpose, mental fatigue, creativity crisis). At the other pole, we have flows of creative work located in digitalization, in immateriality and in the platformization of productive processes. These flows are mediated by technicalities (concentrate this immateriality and focus on experience, understanding the internet as a possible work tool) and rituals (routinization of creative everyday life and the internet as a workspace). In the other direction of the map, between times and spaces of creative work, we have the temporality of urgency and multitasking, as well as the spatialities of public/private mixed in the same domestic and professional daily lives. The times of creative work are mediated by multi-attention identities and by the technicalities of the internet as a tool. In turn, the spaces of creative work concentrate the cognitivities of motivation and mobilization (subjectivities) and the notion of “potentially creative space” for work, as well as the rituals of the internet as a space (working on the internet) possible for expression and production of the creative worker.